EFFECT OF ROCK PHOSPHATE AND CORN COB BIOCHAR ON THE INTENSITY OF PEST DISEASE ATTACKS AND PRODUCTION SOYBEAN CROPS IN DRY ACID LAND - Meithasari, Dian; Endriani, endriani (Jurnal Agrotek Tropika, 2025)
Efforts to increase soybean production can be done in various ways, one of which is planting soybean varieties that are resistant to attacks pests and diseases, as well as acidic land conditions.The use of rock phosphate and biochar has been widely used to improve land conditions.The research aims to determine the effect of rock phosphate and biochar on the intensity of pests and diseases of soybean variety Demas-1. The research was carried out at Natar Experimental Garden, Negara Ratu Village, Natar District, South Lampung Regency. Ultisols soil type with medium soil fertility, soil pH 4.8. The research location is at coordinates 05 o 19’17"South Latitude and 105 o 10’29" East Longitude, with an altitude of 131.9 m above sea level. The research was carried out from March to June 2019. The research used a two-factor Randomized Block Design, namely Corn cob Biochar (A) and Rock phosphate (B) treatment, with 3 replications using the soybean variety Demas-1. The results showed , the level of rust disease attack for the Demas-1 variety was quite resistant, leaf rust attacks ranged from 3.3% - 7.33%, whereas in the A1B1 treatment without rock phosphate and biochar there were no rust disease attacks. These results indicate that Demas-1 plants are resistant to leaf rust disease. On plants aged 65 HST, armyworm attacks in each treatment were not significantly different, attacks reached 34%, the category of attacks that occurred on soybean plants was included in the "medium" category, ranging between >20-<45%. Application of biochar doses of 6, 8 and 10 tons ha -1 tended to increase plant growth, in the characteristics of plant height, number of branches, number of filled pods and seed weight of the Demas-1 variety soybean planting.